2017
DOI: 10.1186/s12888-017-1569-7
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in patterns of drug use and sexual risky behaviour among crack cocaine users in Central Brazil

Abstract: BackgroundThe aim of this study was to compare sociodemographic characteristics, patterns of drug use, and risky sexual behaviour among female and male users of crack cocaine.MethodsBetween 2012 and 2013, we conducted a cross-sectional study of 919 crack cocaine users (783 men and 136 women) in Central Brazil using face-to-face interviews. Blood samples were collected to test for syphilis. The Chi-Square Automatic Interaction Detector (CHAID) was used to explore the differences between genders. We implemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 30 publications
4
24
0
15
Order By: Relevance
“…For instance, our previous study with men revealed that men's sexual experiences have less impact in their risky behaviors (32). Socio economic status of female SUDs are more affected than men such as exchanging sex for money or shelter similar to our findings (57,58). (32).…”
Section: Discussionsupporting
confidence: 91%
“…For instance, our previous study with men revealed that men's sexual experiences have less impact in their risky behaviors (32). Socio economic status of female SUDs are more affected than men such as exchanging sex for money or shelter similar to our findings (57,58). (32).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings reinforce that among those with CUD, males and females suffer from different consequences of drug use [8, 11, 12, 45, 46]. This work advances in comparison to a similar previous investigations on sex differences that assessed indexes of disease severity in crack cocaine users [11, 25], since we assessed a larger sample, but most importantly because we considered testing in multiple potentially impacted domains of life, using reliable and valid measures of it. Furthermore, we tested results on the severity of psychosocial problems considering the interference of comorbidities and problems in other areas of life, specially exposure to childhood maltreatment and lifetime victimization.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, females showed higher HIV prevalence rates and more common sexual abuse history [11]. Similarly, other Brazilian study with 919 crack cocaine users revealed that males report higher lifetime polydrug use, while females have a higher prevalence of syphilis and report to consume higher crack cocaine amounts, and to had more often positive history of prostitution and sexual victimization [25]. In addition, a study with 227 cocaine users revealed that females have higher rates of bipolar disorder, posttraumatic stress disorder and psychotic-induced disorders [26].…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis found that male (three times) and female (two times) current other drug users were significantly more likely to self-report STIs in the last 12 months compared with never users. According to the literature, when males use illicit drugs, they tend to use them with greater frequency, magnitude, and are more likely to engage in simultaneous poly-drug use compared with females 49,50. Our results suggest that 1 in 12 post-secondary students engage in current other drug use regardless of their knowledge and setting.…”
Section: Discussionmentioning
confidence: 49%